Modeling (not so) rare developmental disorders associated with mutations in the protein-tyrosine phosphatase SHP2 - Solman, Maja; Woutersen, Daniëlle T. J.; den Hertog, Jeroen (Frontiers in Cell and Developmental Biology, 2022)
Src homology region 2 (SH2)-containing protein tyrosine phosphatase 2 (SHP2) is a highly conserved protein tyrosine phosphatase (PTP), which is encoded by PTPN11 and is indispensable during embryonic development. Mutations in PTPN11 in human patients cause aberrant signaling of SHP2, resulting in multiple rare hereditary diseases, including Noonan Syndrome (NS), Noonan Syndrome with Multiple Lentigines (NSML), Juvenile Myelomonocytic Leukemia (JMML) and Metachondromatosis (MC). Somatic mutations in PTPN11 have been found to cause cancer. Here, we focus on the role of SHP2 variants in rare diseases and advances in the understanding of its pathogenesis using model systems.